Tantangan Manajemen SDM dalam Menghadapi Generasi Z di Dunia Kerja Modern - Nazwa Aulia Nurzahra; Tamara Nuramalia; Zakia Suci Amalia; Sri Mulyeni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The development of digital technology and changing dynamics of the modern workplace have brought new challenges to human resource (HRM) management, particularly in addressing the characteristics of Generation Z as a new workforce. Generation Z is known as a generation born and raised in the digital era, thus possessing different mindsets, communication styles, and work expectations than previous generations. This study aims to analyze the challenges of HRM management in dealing with Generation Z in the modern workplace and formulate adaptive strategies that organizations can implement. The research method used was a qualitative approach with a literature review through data collection from relevant scientific journals and research articles. The results indicate that the main challenges faced by organizations include high turnover rates, changing communication patterns, the need for work flexibility, demands for mental well-being, and the acceleration of digital transformation. Generation Z prefers a participatory leadership style, a supportive work environment, and opportunities for continuous personal development. Organizations need to implement more flexible, humanistic, and technology-based HRM strategies to increase the loyalty and productivity of young employees. The study's conclusion confirms that organizational success in dealing with Generation Z is largely determined by the ability of HRM management to integrate technology with a people-centric leadership approach.